From smoke to sustainability: the role of socioeconomic factors in the continuous use of clean cooking technologies in Uganda - Katutsi, Vincent Patsy; Kaberuka, Will; Ngoma, Muhammed; Yawe, Bruno Lule; Atukunda, Ronnett; Turyareba, Dickson (Emerald, 2023)
Purpose This study aims to investigate the influence of specific socioeconomic factors, namely neighborhood, gender roles and affordability, on the continuous use of clean cooking technologies (CCTs) in households, using evidence from Uganda. Design/methodology/approach This study adopted an explanatory quantitative design. A questionnaire survey with 379 clean household responses was conducted. The data were analyzed using the Smart Partial Least Squares (PLS) software. Findings The results indicate that the sustained use of clean cooking technologies in households in Uganda is significantly associated with neighborhood influence, shared gender roles and affordability, collectively accounting for 27.7% of the variance. Research limitations/implications The three dimensions of socioeconomic factors under study partially explain the sustained use of CCTs in Uganda. The study does not delve into other socioeconomic factors that could probably account for 72.2% of the variance not explained. The quantitative design may have overlooked the social reality perspectives inherent in qualitative studies that other researchers may endeavor to exploit. Originality/value The authors integrated three dimensions of socioeconomic factors – neighborhood influence, gender roles and affordability – with the diffusion of innovation theory (DIT) using Smart PLS to explain the continuous use of CCTs within households.